2019
DOI: 10.3390/polym11081325
|View full text |Cite
|
Sign up to set email alerts
|

(PVA/Chitosan/Fucoidan)-Ampicillin: A Bioartificial Polymeric Material with Combined Properties in Cell Regeneration and Potential Antibacterial Features

Abstract: Chitosan, fucoidan, and polyvinyl alcohol are categorized as polymers with biomedical applications. Ampicillin, on the other hand, is considered as an important antibiotic that has shown effectivity in both gram-positive and gram-negative micro-organisms. The aforementioned polymers possess unique properties that are considered desirable for cell regeneration although they exhibit drawbacks that can affect their final application. Therefore, films of these biomaterials were prepared and they were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Samples PLA_DC and PLA_DC_EDAC exhibited the highest cytocompatibility. This result was expected as the plasma treatment increased the hydrophilic character of PLA and the wettability of the surface affects cell behavior, especially the cell attachment [37][38][39][40][41]. However, without further immobilization of chlorhexidine, these samples did not exhibit any antibacterial effect.…”
Section: Cytocompatibility Resultsmentioning
confidence: 85%
“…Samples PLA_DC and PLA_DC_EDAC exhibited the highest cytocompatibility. This result was expected as the plasma treatment increased the hydrophilic character of PLA and the wettability of the surface affects cell behavior, especially the cell attachment [37][38][39][40][41]. However, without further immobilization of chlorhexidine, these samples did not exhibit any antibacterial effect.…”
Section: Cytocompatibility Resultsmentioning
confidence: 85%
“…In the case of CS and CS/PVA-PD-FeO NPs (0.01%), treated samples were not observed to have half of the minimum inhibitory concentration (IC 50 ). Several studies reported that chitosan and polyvinyl alcohol showed substantial cell proliferation and a biocompatible nature, which suggests the existence of primary hydroxyl, acetyl, and amine functionalities and its ratio [ 68 , 69 , 70 , 71 , 72 ]. Further, AO/EB fluorescence staining showed a greater number of viable cells in various samples treatment, but in PD-FeO NPs alone, treatment showed fewer apoptotic cells ( Figure 10 ).…”
Section: Resultsmentioning
confidence: 99%
“…Neat PVA is characterized by absorption bands at 3550–3200 cm −1 typical for intermolecular and intramolecular hydrogen bonds in OH (stretching and deformation), 2920 cm −1 (asymmetric CH 2  stretching), 1420 cm −1 (CH bending), 1325 cm −1 (OH bending), 1079 cm −1 (CO stretching) and 820 cm −1 (CC stretching). [ 49 ] It is well known that the OH stretching bands are sensitive to the hydrogen bond. As observed in Figure 1, the FTIR spectra of PVA/GO (Figure 1(A)) and PVA/rGO (Figure 1(B)) nanocomposites are highly similar to that of neat PVA, which indicates that the incorporation of nanoparticles only slightly affected the structure of PVA.…”
Section: Resultsmentioning
confidence: 99%